Konflik Penambangan Batugamping Kecamatan Ponjong dalam Tinjauan Arena Bourdieu - Hilary Reinhart (Department of Urban and Regional Planning, Diponegoro University, 2017)
Limestone mining is a problem in the karst area because it causes environmental degradation, social change from the agrarian to industrial, and conflicts among stakeholders. Therefore, the limestone mining is not only identified as the environmental damage problems but also environmental management problems. The article aimed to explain an overview of the mining conflicts in the karst region. On the other hand, this study also provided a new approach in understanding the conflicts of mining. The study was conducted using qualitative descriptive analysis. Analyses were performed using stakeholder mapping and potential conflicts between stakeholders. The mapping results were contextualized using field and capital approach of Pierre Bourdieu theory. The approach used to understand the direction of conflicts and capital contestation of each author. The capital analysis showed that the government, namely the Energy and Mineral Resources in various levels of bureaucracy has the dominant capital in the arena of limestone mining in Ponjong District because it has a complete capital and outperforms of the other actors. It concludes that the differences types of capital affect the actors to take the position in an arena and each actor who has a robust capital sought to accumulate the capital to attain the main capital.